Advances in the use of CO2 as a renewable feedstock for the synthesis of polymers - Grignard, Bruno; Gennen, Sandro; Jérôme, Christine; Kleij, Arjan W; Detrembleur, Christophe (Chemical Society reviews, 2019)
Carbon dioxide offers an accessible, cheap and renewable carbon feedstock for synthesis. Current interest in the area of carbon dioxide valorisation aims at new, emerging technologies that are able to provide new opportunities to turn a waste into value. Polymers are among the most widely produced chemicals in the world greatly affecting the quality of life. However, there are growing concerns about the lack of reuse of the majority of the consumer plastics and their after-life disposal resulting in an increasing demand for sustainable alternatives. New monomers and polymers that can address these issues are therefore warranted, and merging polymer synthesis with the recycling of carbon dioxide offers a tangible route to transition towards a circular economy. Here, an overview of the most relevant and recent approaches to CO2-based monomers and polymers are highlighted with particular emphasis on the transformation routes used and their involved manifolds.Carbon dioxide offers an accessible, cheap and renewable carbon feedstock for synthesis. Current interest in the area of carbon dioxide valorisation aims at new, emerging technologies that are able to provide new opportunities to turn a waste into value. Polymers are among the most widely produced chemicals in the world greatly affecting the quality of life. However, there are growing concerns about the lack of reuse of the majority of the consumer plastics and their after-life disposal resulting in an increasing demand for sustainable alternatives. New monomers and polymers that can address these issues are therefore warranted, and merging polymer synthesis with the recycling of carbon dioxide offers a tangible route to transition towards a circular economy. Here, an overview of the most relevant and recent approaches to CO2-based monomers and polymers are highlighted with particular emphasis on the transformation routes used and their involved manifolds.